2017
DOI: 10.18632/oncotarget.23146
|View full text |Cite
|
Sign up to set email alerts
|

Jazf1 promotes prostate cancer progression by activating JNK/Slug

Abstract: Juxtaposed with another zinc finger protein 1 (Jazf1) is a zinc finger protein and is known to affect both prostate cancer and type 2 diabetes. Jazf1 inhibits testicular nuclear receptor 4 (TR4) activation through protein-protein interaction, which results in weight loss and alleviates diabetes. However, the role of Jazf1 in prostate cancer is still poorly understood. Hence, we investigated whether the expression of Jazf1 is associated with prostate cancer progression. We confirmed the upregulation of Jazf1 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…It has been proven in many tumours that vimentin plays an important role in tumour invasion and metastasis [38–40], and vimentin promotes GC progression by repressing E-cadherin. Previous studies have shown that JAZF1 promotes Slug expression [24], and because Slug expression significantly increases vimentin expression, this suggests an indirect means by which JAZF1 can regulate vimentin. Now, we demonstrate that JAZF1 can act as a transcriptional activator and bind to the vimentin promoter directly to positively regulate its expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proven in many tumours that vimentin plays an important role in tumour invasion and metastasis [38–40], and vimentin promotes GC progression by repressing E-cadherin. Previous studies have shown that JAZF1 promotes Slug expression [24], and because Slug expression significantly increases vimentin expression, this suggests an indirect means by which JAZF1 can regulate vimentin. Now, we demonstrate that JAZF1 can act as a transcriptional activator and bind to the vimentin promoter directly to positively regulate its expression.…”
Section: Discussionmentioning
confidence: 99%
“…JAZF1 as a transcriptional repressor of TR4, previous studies focused on JAZF1 function in gluconeogenesis regulation and diabetes [17, 36, 37]. Additionally, JAZF1 functions in malignancies, especially endometrial stromal tumours and prostate cancer [2224]. Rearrangement of JAZF1-SUZ12 in endometrial stromal tumours exacerbates cancer by repressing the PRC2 complex to inhibit histone methyltransferase [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since we observed similar effects in HeLa Kyoto cells, it is likely that JAZF1, together with TIP60, is a general and cell-type-independent regulator of ribosome pathways. Nevertheless, since deregulation of JAZF1 expression has been strongly correlated with type 2 diabetes (T2D) and oncogenesis [ 65 , 66 , 67 , 68 , 69 ] in many studies, it is probable that the transcriptional regulatory function of this zinc finger protein is of particular importance in islet or cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…TGFB1I1 (Transforming growth factor beta 1 induced transcript 1) is a coactivator of the androgen receptor, it is known to be associated with prostate cancer, and it can induce EMT, at least in astrocytomes. From the Fisher gene set, JAZF1 (JAZF zinc finger 1) has been shown to promote prostate cancer progression through JNK/Slug, leading to enhanced EMT [65]. Although these genes are just examples of genes identified by our analysis and the processes they may be involved in, this list seems to be a clear confirmation of the importance of EMT in prostate cancer [66].…”
Section: Specific Gene Clusters and Individual Genesmentioning
confidence: 57%